Attitude of Nursing Mothers Towards Exclusive Breastfeeding: A Study of Owerri Municipal Council, Imo State - Ibhafidon, Akhere; Eze-Ufodiama, Stella C.; Ogueri, E.O. (International Journal of Human Kinetics, Health and Education, 2023)
This study was aimed at ascertaining the attitude of nursing mothers towards exclusive breastfeeding in Owerri Municipal Council Area of Imo State. Five objectives, five research questions and four (4) research hypotheses were formulated for the study. Descriptive survey research design was adopted for the study. A sample of three hundred (300) nursing mothers was used for the study. Multi-stage sampling technique was adopted for the research. The researcher made use of a validated and reliable questionnaire with a correlated coefficient of 0.84. Data collected was analysed using descriptive statistics of frequency count and percentage, as well as inferential statistics of chi-square (x2) to test the research hypotheses. The results showed that majority of the nursing mothers in Owerri Municipality have negative attitude towards exclusive breastfeeding. Based on the findings, it was concluded that level of education has a major influence on the attitude of nursing mothers towards exclusive breastfeeding. As such, it was recommended that all nursing mothers should be educated and sensitized through conferences, seminars and workshops by health workers and allied educators, so that most nursing mothers will develop positive attitude towards exclusive breastfeeding, in order to reduce the high rate of infant morbidity and mortality in Owerri Municipal Council Area of Imo State.